The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1080/21606544.2017.1335241
|View full text |Cite
|
Sign up to set email alerts
|

Water quality and recreational use of public waterways

Abstract: This study combines routinely collected water quality data from Ireland and an on-site survey of waterway users to evaluate whether trip duration is responsive to changes in water quality. Four categories of recreational users are considered: anglers, boaters, other water sports (e.g. rowing, swimming, canoeing, etc.) and land-based activities at water sites, specifically walking and cycling. Water quality measures included in the analysis include Water Framework Directive (WFD) status, biochemical oxygen dema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 42 publications
0
15
1
Order By: Relevance
“…In addition, they describe an improvement in the water quality by enriching the water with oxygen. The authors of this paper have not found any published references to the statements provided by the company that supplies the system [7] The results obtained in s'Estany Petit in Mallorca show an increase of oxygen levels despite the increase of conductivity and the warm temperature of the water, both factors associated with difficulties in the incorporation of oxygen into water. It must be considered that the wake-park built in s'Estany Petit is a small one, that only allows one skier per circuit.…”
Section: Discussionmentioning
confidence: 81%
“…In addition, they describe an improvement in the water quality by enriching the water with oxygen. The authors of this paper have not found any published references to the statements provided by the company that supplies the system [7] The results obtained in s'Estany Petit in Mallorca show an increase of oxygen levels despite the increase of conductivity and the warm temperature of the water, both factors associated with difficulties in the incorporation of oxygen into water. It must be considered that the wake-park built in s'Estany Petit is a small one, that only allows one skier per circuit.…”
Section: Discussionmentioning
confidence: 81%
“…Instead, DO will affect the microbiological activity and chemical oxidation in several metals such as iron (27). Meanwhile, eutrophic is most commonly experienced by people who swim at public baths (29). When waters have gone through eutrophication, it becomes progressively enriched with minerals and nutrients.…”
Section: Chemical Quality Of Public Bath Watermentioning
confidence: 99%
“…At least 50% of the adult population in the world visits the public water areas such as beaches, islands, etc. for recreational purposes [1]. Beachgoers rarely receive water quality information, whether the waters are suitable for recreational activity or vice versa.…”
Section: Introductionmentioning
confidence: 99%
“…The risk of exposure to microbial contamination can be reduced by informing beachgoers in advance about the water quality. Recreational water activities improve when the water has better quality [2], [3] but users do not always recognise poor water quality or its associated health risks [1]. Coastal recreational activities are rapid development of economy and urbanisation can promise highly to expose to nearest water resources including the coastal area that ultimately embraces poor water quality severely by time excluding the existing harmful microbiology in the coastal ocean area.…”
Section: Introductionmentioning
confidence: 99%